(untitled) (Editora Impacto Científico, 2025)
This text explores the integration of education for citizenship and sustainability as fundamental pillars in the training of basic education students. Through thorough research, the study analyzes the importance of ethical training and social values ​​as essential elements to promote transformative and meaningful education. The role of educational projects in implementing these concepts is highlighted, providing students with the opportunity to develop a critical and practical understanding of their role as responsible and conscious citizens. The research combined a comprehensive literature review and qualitative data analysis, revealing the urgent need for pedagogical strategies that combine theory with sustainable and civic practices. It is concluded that education for citizenship and sustainability must be an integral part of the curriculum, preparing students to face current and future challenges in an ethical and responsible manner. DOI: https://doi.org/10.56238/edimpacto2025.092-018